EFL Students’ Perspectives as Peer Reviewers in Virtual Writing Contexts: A Case Study in Indonesian Higher Education - Febriyanti, Rina Husnaini; Sundari, Hanna; Baron, Rifari; Rahman, Arif; Arfani, Sri (JOLLT Journal of Languages and Language Teaching, 2025)
The studies of peer review in EFL composition class have received considerable attention in the literature. However, little understanding of how students as reviewers perceived peer review in a virtual learning environment as part of remote assessment. Due to the expansion of technology and the implementation of hybrid learning, language instructions were shifted from an on-site (face-to-face) learning mode into a blended learning system, including language assessment activities. Although existing research on peer review has been extensive, peer review from a peer reviewer perpectives in the virtual setting is still infrequent. This research aims to investigate EFL students’ perspectives as peer reviewers in virtual writing contexts in Indonesian Higher Education. The current study was conducted in an exploratory case study approach. The participants were 41 students. The instruments were open-ended questionnaires and in-depth interviews. In addition, the comment analysis from the peer reviewers was investigated from the rubric of the peer review form. The findings revealed that almost all the peer reviewers voiced positive repertoires regarding the experiences in peer review in a virtual learning environment, and the comment analysis found mostly in the micro and macro meanings and strength comments as the crucial parts in delivering review to the peer revieweesâ€™ artefacts. Â The findings revealed that almost all the peer reviewers voiced positive repertoires regarding the experiences in peer review in a virtual learning environment, and the comment analysis found mostly the micro and macro meanings and strength comments as the crucial parts in delivering review to the peer revieweesâ€™ artefacts. The current study implies sharing recommendations for implementing peer review in the virtual writing context with proper preparation before the realization.